"My Name Is Sally Brown, and I Hate School!": A retrospective study of school liking among conventional and Montessori school alumni. Issue 3 (26th July 2022) - Snyder, Allyson; LeBoeuf, Lee; Lillard, Angeline S.
Abstract: School liking shows clear associations with academic success, yet we know little about how it changes over levels of schooling, what predicts liking school at each level, or how attending alternative schools like Montessori might impact liking. To better understand school liking across time and education settings, we surveyed adults about how much they remember liking elementary, middle, and high school, and identified key school features that predicted higher school liking at each level. Because Montessori schools have many features that other literature suggests predict higher school liking, we purposely sampled Montessori alumni as well, and compared their schools' features for elementary school only (due to sample size). Moreover, we collected open‐ended responses about what participants in both conventional and Montessori liked least about school, revealing what features of their school experiences might have led to less overall school liking. The unique contributions of this study are (1) showing how a wide range of school features predict recalled school liking, (2) examining data for all school levels using a single sample of participants, and (3) comparing recalled school liking and its predictors across conventional and Montessori schools. The sample included 630 adults, of whom 436 were conventional school alumni and 187 were Montessori alumni (7 participants did not report school type). Participants' mean age was 35.8 years ( SD  = 10.53, range = 19–77), and 53% were female. Participants were recruited online, and they responded to Qualtrics surveys about school liking, school features, and their demographics. School liking overall was tepid, and was highest in elementary and lowest in middle school. For all participants, recalling a sense of community and interest in schoolwork were most strongly associated with school liking. Adults who attended schools which emphasized studying topics of personal interest and rewards for positive behavior also liked school more. Montessori school alumni reported higher school liking and that learning was what they liked most about school; by contrast, conventional school alumni most liked seeing friends. Levels of school liking, as recalled by adults, are low overall, but are higher in elementary school and higher amongst those who recall their schools as having stronger community, catering more to student interest, and rewarding positive behavior. In addition, school liking was higher among people who attended Montessori schools. Further research could extend to a cross‐sectional study of children currently enrolled in different types of schools. Practitioner points: 1. Adults remember liking elementary school the most and middle school the least. 2. Feeling a sense of community and having an interest in schoolwork were the strongest predictors of school liking. 3. Adults who had attended Montessori schools remembered liking school more than adults who attended conventional schools